2014
DOI: 10.1371/journal.pone.0086874
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Increasing the Release of Mouse β- Defensin-14 in the Treatment of Osteomyelitis in Mice: A Primary Study

Abstract: Mammalian β-defensins are small cationic peptides that have been implicated in mediating innate immune defenses against microbial infection. Mouse β-defensin-14 (MBD-14), based on structural and functional similarities, appears to be an ortholog of human β-defensin-3 (HBD-3). Previous studies identified signaling pathway p38 mitogen-activated protein kinase (MAPK) that contributed to the expression of MBD-14 in mouse osteoblasts upon contacted with methicillin-resistance Staphylococcus aureus (MRSA) supernatan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…Our recent studies identified that when mouse osteoblasts contacted with MRSA supernatant, the relevant activated signaling pathway p38 mitogen-activated protein kinase could contribute to the obvious release of MBD-14, which is the structural and functional ortholog of HBD-3 [43,44]. Meanwhile, we also indicated the potential role of increasing the release of MBD-14 in the treatment of osteomyelitis in mice [22,45]. In addition to their role of local high Fig.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our recent studies identified that when mouse osteoblasts contacted with MRSA supernatant, the relevant activated signaling pathway p38 mitogen-activated protein kinase could contribute to the obvious release of MBD-14, which is the structural and functional ortholog of HBD-3 [43,44]. Meanwhile, we also indicated the potential role of increasing the release of MBD-14 in the treatment of osteomyelitis in mice [22,45]. In addition to their role of local high Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Animals were prepared for surgery as follows: the back of the mice was shaved, depilated, and disinfected with alcohol. To provide sterile conditions during surgery, animals were placed on sterile drapes and bodies were covered with sterile sheets [22]. Subsequently, two biofilm-infected titanium plates, which had been gently washed thrice with PBS to remove nonadherent bacteria, were implanted subcutaneously bilateral to the spine, as reported previously, with one plate on each side [8] (Fig.…”
Section: 5mentioning
confidence: 99%
“…66 In one interesting study, a murine model for the study of human levels. 55 In a following study, infections in mice treated with HBD-3…”
Section: Antimicrobial Peptidesmentioning
confidence: 97%
“…Antimicrobial peptides (AMPs), found naturally within human neutrophils and in epithelial secretions, have gained popularity in recent years as therapeutics for osteomyelitis. 53 The list of AMPs is extensive, 54 but some investigated for S. aureus clearance include: β-defensins, 55,56 Magainin 2 (also known by its analog, pexiganan acetate), 57,58 human lactoferrin 1-11 (hLF1-11), 59,60 isolates of bee venom, [61][62][63][64] snake venom, 65 and L-homocarnosine. 66 In one interesting study, a murine model for the study of human levels.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…The expression levels of IL-10, TNF-α, IL-1α and IP-10 in the model group at each time-point were significantly higher than the other two groups, and the difference was statistically significant; in terms of the comparison between the HBD-3 group and vancomycin group, the difference was not statistically significant. It was suggested that HBD-3 and vancomycin could significantly reduce the IL-10, TNF-α, IL-1α and IP-10 mediated inflammatory response (14). In conclusion, β-defensin 3 can inhibit the bacterial growth by regulating inflammation and immune response in MRSA-induced implant drug-resistant bacteria biofilm infection in mouse tibial bone marrow.…”
Section: Discussionmentioning
confidence: 99%